Sosialisasi Penggunaan Media Kartika untuk Meningkatkan Motivasi Belajar Matematika Siswa SD Negeri No. 46 Songing Kabupaten Sinjai - Muhammad Awal Nur; Nursalim Nursalim; Abd. Hafid; Rosmalah Rosmalah; Awaluddin Muin (Lamahu: Jurnal Pengabdian Masyarakat Terintegrasi, 2025)
The learning motivation of students at SD Negeri 46 Songing in mathematics is still considered low. This condition is evident from the students' mathematics learning outcomes, which are generally below average. In addition, there is minimal use of instructional media in the teaching process, as well as data from the 2024 Education Report, which indicates that students’ numeracy skills are categorized as moderate. Therefore, this outreach activity aims to introduce and provide training for teachers on how to optimize the use of KARTIKA (Mathematics Cards) as a teaching medium, with the goal of improving students’ learning motivation and foundational mathematical abilities.The activity was carried out through socialization and hands-on practice using five planned stages: (1) preparation, (2) media design, (3) dissemination, (4) training and mentoring, and (5) evaluation and follow-up. Each stage was implemented systematically and involved active participation from the stakeholders, especially classroom teachers and students of SD Negeri 46 Songing.The results of the community service activity showed that the use of KARTIKA (Mathematics Cards) can increase students’ learning motivation and create a more interactive and enjoyable learning environment, with an average score of 4.46, categorized as good. Meanwhile, the teacher questionnaire results indicated enthusiasm and openness to integrating the KARTIKA media into classroom instruction, with an average score of 4.7, categorized as very good. The KARTIKA media has proven to be an effective alternative tool for enhancing students’ motivation to learn mathematics at the elementary school level.